A review of the interactive marketing literature in the context of personal selling and sales management. Issue 4 (7th October 2014) - Rodriguez, Michael; L. Dixon, Andrea; W. Peltier, James
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this 16-year review is to summarize interactive marketing literature in the context of personal selling and sales management. This paper serves as precursor to the Special Issue on the Convergence of Interactive Marketing and Personal Selling and Sales Management to be published by the Journal of Research in Interactive Marketing. Key research needs are identified. Design/methodology/approach – A content analysis was performed on 106 articles categorized over 1998-2013. Ebsco Host was used as the database search engine, running impendent searches using personal selling, professional selling and sales management as identifiers across a variety of interactive marketing topics identified by Journal of Research in Interactive Marketing (JRIM)'s Editorial Board. Findings – The examination of the convergence of interactive marketing in a personal selling/sales management context revealed 106 articles, with approximately 60 per cent being published in the past eight years. Although the interactive marking field is growing, there is clearly a significant opportunity for scholarly work across wide-ranging personal selling and sales management topics, and specifically in the areas of performance indices, evolving technologies, social media and tactical sales and management issues. Practical implications – The paper reviews personal selling and sales management articles that have been published in the time period of 1998-2013 across marketing, business and non-business journals. While the Journal of Personal Selling and Sales Management has been the dominant outlet, other marketing and non-marketing journals are increasing their exposure in these areas. Originality/value – The study provides both academics and practitioners with an updated review of the interactive marketing literature along with a sense of how personal selling and sales management research is evolving. This review offers value as a standalone article and as input for scholars submitting manuscripts to JRIM's Special Issue on the Convergence of Interactive Marketing and Personal Selling and Sales Management.